Job stress and burnout among librarians in selected special libraries in Metro Manila - Mohammad, Satrina V. (2001)
Stress may be either functional or dysfunctional in the workplace. It may be viewed as a continuum of stress, distress or strain, and burnout. The sources of job stress and burnout are organizational, and job and career stressors. Stress and burnout manifest in both physical and behavioral occurrences. The level of perceived burnout may vary depending on certain personal and professional characteristics.